Pengaruh Biaya Lingkungan, Investasi Eco Efficiency Terhadap Profitabilitas pada Perusahaan Energi yang Terdaftar di BEI Tahun 2022-2024 - Sherlyn Carolina; Cherrya Dhia Wenny (Universitas Multi Data Palembang, 2026)
The purpose of this study is to determine how environmental costs and eco-efficiency investments affect profitability. This research is quantitative, and the data used are secondary data obtained from the Indonesia Stock Exchange (IDX). The population of this study were energy companies listed on the Indonesia Stock Exchange (IDX) in 2022-2024. A sample of 91 companies was used. The sampling technique used was purposive sampling. The analytical method used was multiple linear regression with SPSS 26. The results of this study indicate that environmental costs have a negative and significant effect on profitability, while eco-efficiency investments have no significant effect on profitability.